Detecção molecular de Streptococus agalactiae em amostras de leite bovino obtidas de tanques de expansão - Elias, Acacia Orieth [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Mastitis is the most common infectious disease affecting dairy cattle and remains the most economically important disease of dairy industries around the world. Streptococcus agalactiae is a contagious pathogen that can only survives in the mammary gland, often associated to subclinical mastitis and is highly infectious. The bacteria can cause an increase of bulk tank bacterial counts (BTBC) and somatic cell counts (BTSCC). The microbiological characterization of S.agalactiae in bulk tank samples is an auxiliary method to control contagious mastitis. Therefore there are some limitations with time consuming cultures or identification methods and additional concerns about the conservation and transport of samples. Molecular identification, based on polymerase chain reactions (PCR) can identify the pathogen even when it is not viable for culturing. Bulk tank samples of 247 dairy farms were cultured in 10% bovine blood agar, followed by BTBC and S.agalactiae isolation and biochemical characterization. This gold standard method was then compared to molecular identification. The DNA extraction was taken by cell lyses with proteinase K and a phenol/chloroform protocol. The selected specie specific primers of 16S rRNA genes were used to identify S.agalactiae. Mean values of BTBC were 1,08 x 106 UFC/mL and the bacteria was identified by microbiological methods in 98 (39,6%) and by PCR in 110 (44,5%) of the samples. The results showed a sensibility of 0,8571 l 0,0353 (CI95%=0,7719 - 0,9196) and specificity of 0,8255 l 0,0311 (CI95%=0,7549 - 0,8827). The lack of significant differences of both the microbiological and molecular results (k=0,6686 l 0,0477 and CI95% = 0,5752 - 0,7620) indicated substantial agreement with the methods. This suggests that PCR of bulk tank samples can be used to detect contagious mastitis caused by S.agalactiae.
Keywords: Bovino de leite - Contaminação; Saude animal